Co-pyrolysis of lignocellulosic biomass and plastics: A comprehensive study on pyrolysis kinetics and characteristics - Vo, Thuan Anh; Tran, Quoc Khanh; Ly, Hoang Vu; Kwon, Byeongwan; Hwang, Hyun Tae; Kim, Jinsoo; Kim, Seung-Soo (Journal of analytical and applied pyrolysis, 2022)
Co-pyrolysis of biomass with plastics is an interesting research trend in improving both the yield and quality of oil products toward taking advantage of flexible material resources and sustainable fuel development. This study investigated the kinetic behaviors using thermogravimetric analysis and pyrolysis characterization for the co-pyrolysis of biomass (bamboo and oak wood) with plastics (polypropylene [PP] and polystyrene [PS]) in a fixed-bed reactor. The kinetic triplet for feedstocks was determined using the isoconversional method, compensation effect, and master plot method. The addition of 20 wt% plastics into biomass decreased the activation energy, with the most distinct positive synergistic effect for the bamboo/PS blend. In addition, the effect of co-pyrolysis temperature and biomass/plastic ratio on pyrolysis characteristics was investigated. Through biomass pyrolysis and biomass/plastic co-pyrolysis, the positive changes in distributions and physical-chemical properties of the products (i.e., char, oil, and gas) were observed using various analytical methods. Especially in the case of biomass/PS blends, the synergistic effect of co-pyrolysis was shown due to the difference in the actual and theoretical yields of the products. The liquid yields of the co-pyrolysis were 50.95, 50.17, 55.15, and 56.16 wt% for bamboo/PP, bamboo/PS, oak wood/PP, and oak wood/PS, respectively. The highest HHV of 28.22 MJ/kg was obtained for oil derived from the co-pyrolysis of bamboo/PS. Furthermore, co-pyrolysis chars have high HHVs in the range of 30.73–32.41 MJ/kg, suggesting that they can be used as solid fuels. [Display omitted] •A synergistic effect on co-pyrolysis of biomass/plastic blends was observed.•Kinetic triplet parameters for pyrolysis of individual materials and blends have been identified.•The presence of plastics in the feedstock increases aliphatic/aromatic hydrocarbons content in the oil.•Co-pyrolysis of blends improves both the yield and HHV of the oil.•With increasing temperature, the CO2 content decreases but the CO and H2 contents increase.